Sensorial Interior: Museum Diorama as Phenomenal Space - Edwards, Sarah (Interiority, 2018)
Museum dioramas are widely recognised as historic visual tropes used to frame the grandeur of the outside world within an interior viewing space. With the development of digital technologies, data projection and soundscape have increasingly replaced diorama production as a means to transform these once static-animal-posed-in-painted- habitat with immersive interiors that engage the visual and aural senses alike. Andre Breton proposes that two modes of consciousness exist: an exterior world of facts and an interior world of emotions. These interiors and exteriors produce an interface and exchange. An invitation to respond to the interior of RMIT University’s First Site gallery provided an opportunity to experiment with the three traditional dioramic elements used to bring the exterior world into an interior employing taxidermy, model making and set painting. By engaging digital technologies in response to these three elements, I developed a sensorial interior, where the exterior world of facts was set into dialogue with the interior world of emotion. A physical encounter that expanded on ‘interior’ as an experiential, relational, phenomenal and emotive space.